Kemampuan Menulis Pada Pantun Mata Pelajaran Bahasa Indonesia Teks Puisi Rakyat Kelas VII SMP Negeri 03 Batu (Studi Kasus) - Nur Mahfuzah Saffawati; Ribut Wahyu Eriyanti; Arif Setiawan (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Independent Curriculum learning requires students to be able to master four language skills which include listening, reading, speaking, and writing skills. In Indonesian Language Learning at the Junior High School (SMP) level there is Pantun material that requires students to be able to write papers. This study aims to describe the process of learning to write rhymes and describe the results of learning to write rhymes. The type of research used is qualitative research with a case study approach. The source of the research data was taken from data from class VII A students at SMP Negeri 03 Batu. As for the data collection techniques used in research in the form of observation, interviews and documentation. The research data analysis applies the Miles & Huberman model which has a flow of data reduction activities, data presentation and conclusion/verification. The results of the study show that (1) in the learning process by applying the Project Based Learning (PJBL) learning model, students are more flexible in determining themes, organize a vocabulary that they often read or listen to, arrange selected vocabulary into one sentence, convey a message or message in a poem. (2) The results of the Project Based Learning (PJBL) Learning Process obtained an average score of 83.12. The acquisition of this value has exceeded the minimum completeness criteria (KKM) set by the teacher, namely 75.